25. Solitary metastasis to the pancreas from colon cancer treated with radical surgery: A case report and literature review - Anh, Pham The; Cuong, Truong Manh; Anh, Pham Tuan (Tạp chí Nghiên cứu Y học, 2024)
This report describes a rare case of pancreatic metastasis in a 56-year-old woman with a past medical history of malignancy. The patient initially presented with right breast cancer in 2008, which was treated with a modified radical mastectomy followed by adjuvant chemotherapy. Subsequently, she developed right colon cancer and underwent a right hemicolectomy with adjuvant chemotherapy in 2015. In October 2020, during a routine examination, a suspicious lesion was identified in the duodenum and head of the pancreas. A biopsy confirmed the presence of moderately differentiated adenocarcinoma. Following a comprehensive multidisciplinary consultation, the patient was recommended for exploratory surgery to assess the feasibility of a pancreatoduodenectomy (Whipple procedure) with subsequent ileocolic reanastomosis (reconnection of the ileum to the transverse colon), followed by systemic therapy.